2014
DOI: 10.1111/peps.12071
|View full text |Cite
|
Sign up to set email alerts
|

How Do Leaders and their Teams Bring about Organizational Learning and Outcomes?

Abstract: How do leaders generate a learning climate that yields favorable organizational outcomes? To address this question, we offer and test a model linking charismatic leadership with the team-emergent states of shared vision and trust within the team, as predicting organizational learning climate, and long-term assessments of organizational outcomes by key stakeholders. We examined this model in a sample of 69 Arab elementary schools in Israel using multiple sources of raters, predicting long-term assessments by ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 120 publications
(170 reference statements)
6
89
0
3
Order By: Relevance
“…A further result of the current research related to the effect of principals' inspirational vision content on RACAP. This is in line with previous studies relating school principals with organizational learning (Berson et al, 2015). Specifically, school teachers who perceived the principal's vision as optimistic, inspirational, and presenting challenges and opportunities, were more likely to create something new based on the ''transformed'' knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A further result of the current research related to the effect of principals' inspirational vision content on RACAP. This is in line with previous studies relating school principals with organizational learning (Berson et al, 2015). Specifically, school teachers who perceived the principal's vision as optimistic, inspirational, and presenting challenges and opportunities, were more likely to create something new based on the ''transformed'' knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…We controlled for the effects of school size (i.e., number of teachers employed by the school) and principals' tenure in their jobs, because these variables are potentially relevant to outcomes such as organizational learning (Berson et al, 2015).…”
Section: Controlled Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although trust appears to be multifaceted in nature, these different facets are proposed to be "mutually supportive aspects" that combine psychologically to form a "unitary experience called trust" (Lewis and Weigert 1985, p. 972). In support, numerous intrateam trust studies relying on McAllister's (1995) "multidimensional" scale found the scale to be unidimensional (e.g., Berson et al 2014, Braun et al 2013, Dirks 2000, Mach et al 2010. Consistent with these arguments and the majority of the literature (e.g., Crisp and Jarvenpaa 2013, Joshi et al 2009, Langfred 2004, we therefore conceptualize intrateam trust as a unitary construct.…”
Section: How (Peer) Control Combinations Operatementioning
confidence: 57%
“…Many leadership writings assume that leaders shape group culture and values, and these drive behaviors, which then determine group performance (Deal & Kennedy, 2000; see also Berson, Da'as, & Waldman, 2014;Sun, Xu, & Shang, 2014). For example, transformational leaders, through their powerful analogies, inspiring visions and uplifting stated values (Schein, 1990), produce a "transformational culture," which then in turn influences team performance behavior (i.e., Bass & Avolio, 1993: 119;Parry & Proctor-Thomson, 2003).…”
Section: Leader Humilitymentioning
confidence: 99%